Contributions of MNEs to poverty alleviation through CSR programs: Bangladesh perspective - Hoque, Nazamul; Khan, Mohammad Aktaruzzaman; Bhuiyan, Mohammad Zahid Hossain (IIUC Studies, 2017)
This study examines the contribution of CSR programs of multinational enterprises (MNEs) operating in Bangladesh in the poverty alleviation. The authors employed a mixed-method approach to collect qualitative data by interviewing executives of ten MNEs while for quantitative data annual reports, websites, and articles were consulted. Results depicted insignificant contribution of MNEs in poverty alleviation by their corporate social responsibility (CSR) initiatives. The average contribution of sample MNEs stand at only 0.52 per cent of profits after tax to CSR programs, ranging from 2.96% to 0.15%. The study reveals that most of the MNEs are not contributing as per their financial capacity and they lack a policy of donating a reasonable portion of profit to CSR along with poverty alleviation priority. The study suggests that government of Bangladesh must act sincerely and deliberately for active involvement of MNEs in CSR programs helpful for poverty alleviation by necessary policy framework and motivational supports with a view to accelerate the poverty alleviation movement for a happy, prosperous, and progressive Bangladesh. IIUC Studies Vol.14(2) December 2017: 55-70